THE HISTORY OF THE FORMATION OF THE KOKAND PEDAGOGICAL INSTITUTE - Nuridinov Turdali Qambarovich (Phd); Khushmatov Mirziyo Obloberdi ugli (American Journals, 2022)
This article highlights the issues of education and development of the Kokand Pedagogical Institute.
Keywords: Kokand, the policy of the Soviet government on education, Tashkent, Samarkand, Bukhara, Kokand, higher pedagogical institution, evening higher school. Women's educational institution.